ChemInform Abstract: Hydrogenation of Esters to Alcohols with a Well‐Defined Iron Complex. Issue 6 (23rd January 2015) - Werkmeister, Svenja; Junge, Kathrin; Wendt, Bianca; Alberico, Elisabetta; Jiao, Haijun; Baumann, Wolfgang; Junge, Henrik; Gallou, Fabrice; Beller, Matthias
Abstract The process involves a base‐free reduction in the presence of the novel iron complex AIPC without any additives.